Quantification of fatty acids in the muscle of Antarctic fish Trematomus bernacchii by gas chromatography-mass spectrometry: Optimization of the analytical methodology. (April 2017) - Truzzi, C.; Illuminati, S.; Annibaldi, A.; Antonucci, M.; Scarponi, G.
Abstract: This work presents data on the quantification of fatty acids (FAs, in terms of mass unit per tissue weight) in the muscle of Trematomus bernacchii, a key species in Antarctica, often used as bioindicator for contamination studies. Modifications in fatty acids content should be considered a useful biomarker to study how contaminants affect Antarctic biota. Until now, very few studies quantified fatty acids of muscle of T. bernacchii, and only as percentage of a single fatty acid on total lipids. To perform the quantification of fatty acids, we used an analytical method based on a fast microwave-assisted extraction of lipids from a lyophilized sample, a base-catalyzed trans-esterification of lipid extract to obtain Fatty Acids Methyl Esters (FAMEs), and a separation and identification of FAMEs by gas chromatography-mass spectrometry. With the optimized and validated method, a fast and accurate separation of Fatty Acids Methyl Esters was performed in 43 min. The linearity was checked up to about 320 μg mL −1 ; limit of detection and limit of quantification are in the range 4–22 μg mL −1 and 13–66 μg mL −1, respectively. The optimized method showed a good accuracy and precision. Major fatty acids were 14:0, 16:0, 16:1n7, 18:1n9, 18:1n7, 20:1n9, 20:5n3 and 22:6n3. Quantified FAs compute for about 47 mg g −1 tissue dry weight (dw), with 9.1 ± 0.1 mg g −1  dw of saturated FAs, 25.5 ± 0.1 mg g −1  dw of mono-unsaturated FAs, and 12.2 ± 0.1 mg g −1  dw of poly-unsaturated FAs. Highlights: Fatty acids in muscle of Trematomus bernacchii : set-up of the analytical methodology. Accurate Microwave-assisted extraction of lipids preceded by lyophilization. LOD and LOQ: from ∼4 to ∼22 μg/mL, and from ∼13 to ∼66 μg/mL, respectively. Good accuracy (recovery test ∼96%) and precision (intra-day ≤4%, inter-day ≤7%). Quantified FAs compute 9.1, 25.5, 12.2 mg g −1  dw for SFA, MUFA, PUFA, respectively.